Method for Evaluating the Effect of the Design and the Environmental Conditions of the Manufacturing Cells toImprove Work Performance - Mildrend Montoya-Reyes; Alvaro González-Angeles; Margarita Gil-Samaniego-Ramos; Ismael Mendoza-Muñoz; Juan Ling-López (Journal of Engineering)
A method is proposed to improve work performance through an adequate design of the manufacturing cell along with optimal environmental conditions to contribute to the well-being of the worker. The methodology used was divided into four stages: the first corresponds to the analysis of operations; the second is the analysis of the effect of the design of the manufacturing cell; the third is the evaluation of environmental conditions such as lighting, noise, and temperature to compare them with the official standard and determine if they meet the permitted levels; and the fourth is to conclude and recommend improvements to the manufacturing cell. The method was applied in a company in the automotive industry, where a change was made from a linear cell distribution to an L-shaped distribution, with a 50% reduction in workforce and an increase in the productive time of the worker of 49%. Also, the environmental conditions of the cell comply with the requirements of official standards.